KONSEP PENDIDIKAN TASAWUF (Kajian Tentang Tujuan dan Strategi Pencapaian dalam Pendidikan Tasawuf) - Sodiq, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2014)
Islamic education is uniquely different from othertypes of educational theory and practice largelybecause of the all-encompassing influence of theQur‟an. The Qur‟an serves as a comprehensiveblueprint for both the individual and society and as theprimary source of knowledge. Islamic spiritualityfocuses on the activity al-qalb, or the heart; and alnafsor the self or ego. Purification of the heart (tanqiyaal-qalb) and rectification of the self (tahdhib al-nafs) arefrom the most important of personally obligatory actsand of the imperative Divine commands, as proven bythe Book, the Sunna (tradition), and statements of thescholars. The ultimate aim of Muslim education lies inthe realization of complete submission to Allah on thelevel of the individual, the community and humanity atlarge. And the aim of Islamic spiritual education is to curethe human soul of this fatal malady and to make himwhole as he was in the Adamic state. In other word,the aims are to make man achieve integration in all thedepth and breadth of his being and life. In thefollowing, will be discussed the the concept of tassawufeducation